The Urgency Of Educational Media From Al-Quran Perspective - Dede Tarlan; Ade Fahrizal; Aang Setiawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This paper aims to describe that educational media, according to the Quran, has existed for a long time and holds a special position. One of the most important elements that teachers must know and master in order to make the learning process effective and achieve the learning goals is educational media. The educational media that should be used by teachers in the learning process should be suitable for the material's characteristics, the students' characteristics, and in line with its objectives. In this regard, teachers must pay attention to specific foundations for the use of educational media. The research method used in this writing is library research, which provides a general overview and analysis of the understanding, the reasoning behind using media, the benefits of using media in education, and research findings regarding educational media from the perspective of the Quran. This study found many verses that hint at educational media in line with what has developed in the field of education today. It is interesting to understand that the Quran itself is a guidebook that can provide answers to many life issues, especially in the field of education, particularly regarding educational media. Therefore, it is expected that the results of this study will broaden the insights of teachers to better understand the importance of using educational media from the perspective of the Quran. With the right use of media, learning can be effective, and learning objectives can be maximally achieved.